156. Evaluating Antibiotic Use and Developing a Tool to Optimize Prescribing in a Pediatric HIV Clinic in Eswatini. (31st December 2020) - Streatfield, Ashish E; Ness, Tara; Simelane, Tandzile T; Guffey, Danielle; Lukhele, Bhekemusa; Kay, Alexander
Abstract: Background: Antibiotic resistance is an emerging global health issue, fueled by inadequate surveillance systems and the absence of antimicrobial stewardship. In resource-limited settings, antimicrobial use is often based on clinical evaluation rather than microbiologic evidence, making treatment guidelines and the education of healthcare providers paramount to ensuring appropriate antimicrobial prescribing. In a human immunodeficiency virus (HIV) clinic for children and their families in Eswatini, we sought to understand the use of antibiotics and identify specific areas for improvement. Methods: We performed a retrospective patient chart review as part of a quality improvement (QI) initiative to assess antimicrobial use before and after implementation of a standardized antimicrobial guide. For each prescribing period, 100 random patient encounters were selected for review to observe if the indication for antibiotics, duration, and dose were consistent with World Health Organization (WHO) guidelines. Two physicians reviewed each encounter to determine the appropriateness of antibiotic use using a structured abstraction tool, with a third resolving discrepancies. Results were analyzed using a chi-square test of proportions and a structured survey was performed to assess perceptions of the guide. Results: After the implementation of an antimicrobial guide, there was a significant decrease in the proportion of clinic visits with an antibiotic prescribed (p < 0.001). Incorrect indication for antimicrobial use decreased from 20.4% in the initial period, to 10.31% and 10.2% but did not reach significance (p=.0621) in the subsequent periods after implementation. Incorrect dose/duration decreased from 10.47% in the initial period to 7.37% and 3.1% in the subsequent periods, but this was also was not significant (p = 0.139). All prescribers who completed the survey used the antimicrobial guide and felt that it positively impacted their prescribing patterns. Conclusion: Our study found that an antibiotic guide reduced and improved the prescription of antimicrobials. Antimicrobial stewardship is a global problem and this data demonstrates that practical solutions can have a lasting impact on antimicrobial prescribing in low resource settings. Disclosures: All Authors : No reported disclosures